Symmetry, phase states and dynamics of magnets with spin s=1 - Kovalevsky, M.Y.; Kotelnikova, O.A. (Вопросы атомной науки и техники, 2012)
The results of investigations of magnets with spin s=1 are presented. The analysis of the possible symmetry of exchange interactions and its relationship with the magnetic degrees of freedom was done. We formulate the dynamics of normal non-equilibrium states. The generalization of the Bloch equations is obtained and the effect of magnetic field on the spectral characteristics is considered. The influence of dissipative processes is investigated and the relaxation fluxes corresponding to the exchange symmetry of the magnetic Hamiltonian are obtained. Представлены результаты исследований магнетиков со спином 1. Дан анализ возможной симметрии обменных взаимодействий и ее связь с магнитными степенями свободы. Сформулирована динамика нормальных неравновесных состояний. Получено обобщение уравнения Блоха и изучено влияние магнитного поля на спектральные характеристики. Рассмотрено влияние диссипативных процессов и найдены релаксационные потоки, обусловленные обменной симметрией магнитного гамильтониана. Представлені результати досліджень магнетиків зі спіном 1. Дано аналіз можливої симетрії обмінних взаємодій та їх зв'язок з магнітними ступенями свободи. Сформульована динаміка нормальних нерівноважних станів. Отримано узагальнення рівняння Блоха і вивчено вплив магнітного поля на спектральні характеристики. Розглянуто вплив дисипативних процесів і знайдені релаксаційні потоки, зумовлені обмінної симетрією магнітного гамільтоніана.